Effect of an additional gonadotropin-releasing hormone 2 days after the initiation of a resynchronization program 25 days after artificial insemination on fertility of lactating dairy cows - Iago Matheus Rosa Leão; Anthony Carbajal; César Narciso; Carlos Eduardo Cardoso Consentini; Roberto Sartori; João Paulo Nascimento Martins (JDS Communications)
We investigated the effect of an additional GnRH 2 d after initiation of resynchronization on d 25 post-AI on the proportion of cows without a corpus luteum (CL) at nonpregnancy diagnosis (NPD) and pregnancy per AI (P/AI) of cows with a CL at NPD that were reinseminated. Once per week, cows that were inseminated 25 d earlier were randomly assigned to receive either a GnRH treatment only (G25) or GnRH on this day and 2 d later (G25&27). Pregnancy diagnosis and CL presence were determined d 32 post-AI using ultrasonography. Nonpregnant cows with a CL were enrolled in different strategies for resynchronization of ovulation according to parity (primiparous or multiparous) and CL size. Primiparous and multiparous cows with a CL ≥20 mm in diameter continued Resynch-25 (PGF2α on d 32; PGF2α on d 33; GnRH on d 34; and AI on d 35). Multiparous cows with CL <20 mm restarted a modified Ovsynch at NPD (GnRH – 7 d – PGF2α – 1 d – PGF2α – 1 d – GnRH – 1 d – AI). Primiparous cows with CL diameter <20 mm started an Ovsynch+CIDR protocol on the day of NPD (GnRH + CIDR inserted – 7 d – PGF2α + CIDR removed – 1 d – PGF2α – 1 d – GnRH – 1 d – AI). Cows without a CL were not enrolled in any resynchronization program for a week and were excluded from fertility analyses. In multiparous cows only, the additional d 27 GnRH treatment was associated with a decreased P/AI 32 d and 102 d post-AI for the AI before treatment. The overall proportion of nonpregnant cows without CL did not differ between treatments. Yet, the GnRH treatment 27 d after AI tended to increase the proportion of overall nonpregnant cows with CL <20 mm at NPD. Treatment did not affect fertility parameters of primiparous cows with a CL ≥20 mm that continued Resynch-25 at NPD. Primiparous cows in G25&27 with CL <20 mm and submitted to Ovsynch+CIDR at NPD tended to have decreased P/AI 102 d after AI and calving/AI. When fertility parameters of primiparous cows with a CL independent of size at NPD were analyzed combined, no effect of treatment was observed. Treatment did not affect fertility of multiparous cows with CL <20 mm enrolled in Ovsynch at NPD. Multiparous cows in the G25&27 group that had a CL ≥20 mm and continued Resynch-25 at NPD tended to have a greater calving/AI due to a decreased total pregnancy loss. In summary, no treatment effect was observed on the overall fertility of primiparous cows with CL at NPD. In multiparous cows, G25&27 was associated with a decreased fertility of the previous AI, but it tended to increase calving/AI for multiparous cows with CL at NPD by decreasing the total pregnancy loss for the AI after treatment.